Drug-Induced Reorganisation of Lipid Metabolism Limits the Therapeutic Efficacy of Ponatinib in Glioma Stem Cells - Paula Aldaz; Ana Olias-Arjona; Irene Lasheras-Otero; Karina Ausin; Marta Redondo-Muñoz; Claudia Wellbrock; Enrique Santamaria; Joaquin Fernandez-Irigoyen; Imanol Arozarena (MDPI AG, 2024)
The standard of care for glioblastoma (GBM) involves surgery followed by adjuvant radio- and chemotherapy, but often within months, patients relapse, and this has been linked to glioma stem cells (GSCs), self-renewing cells with increased therapy resistance. The identification of the epidermal growth factor receptor (EGFR) and platelet-derived growth factor receptor (PDGFR) as key players in gliomagenesis inspired the development of inhibitors targeting these tyrosine kinases (TKIs). However, results from clinical trials testing TKIs have been disappointing, and while the role of GSCs in conventional therapy resistance has been extensively studied, less is known about resistance of GSCs to TKIs. In this study, we have used compartmentalised proteomics to analyse the adaptive response of GSCs to ponatinib, a TKI with activity against PDGFR. The analysis of differentially expressed proteins revealed that GSCs respond to ponatinib by broadly rewiring lipid metabolism, involving fatty acid beta-oxidation, cholesterol synthesis, and sphingolipid degradation. Inhibiting each of these metabolic pathways overcame ponatinib adaptation of GSCs, but interrogation of patient data revealed sphingolipid degradation as the most relevant pathway in GBM. Our data highlight that targeting lipid metabolism, and particularly sphingolipid degradation in combinatorial therapies, could improve the outcome of TKI therapies using ponatinib in GBM.